USER AUTHENTICATION JARINGAN NIRKABEL BERBASIS WEB MENGGUNAKAN RADIUS DI UNIVERSITAS BALE BANDUNG (UNIBBA) - Muchamad Rusdan; Asep Ririh Riswaya (STMIK Mardira Indonesia, Bandung, 2018)
In this study, problems arise due to the use of WPA2-based user authentication. Constraints faced in using WPA2 are difficult to distinguish between users of wireless network services that are permitted and not permitted. The purpose of this study is that each wireless network user at Bale Bandung University (UNIBBA) can be distinguished between users who are permitted and not permitted so that wireless networks become safe, comfortable and user-friendly. UNIBBA is one of the educational institutions in Bandung Regency, which makes wireless networks a standard facility provided to students, lecturers, and employees that can be accessed through mobile devices that support wireless networks. The research method used is the waterfall method. The results of this study created a web-based wireless network user authentication system using RADIUS that is safe and user-friendly, by testing on the RADIUS server side and web login form.Keywords:user authentication, RADIUS, waterfall, wireless network DOI 10.5281/zenodo.3373720